Support of research vessels in the Antarctic with NRT radar information: an innovative service at DLR's Antarctic station GARS O’Higgins - Höppner, Kathrin; Schättler, Birgit; Schwarz, Egbert; Krause, Detmar; Diedrich, Erhard; Metzig, Robert; Schröder, Michael; Wesche, Christine (2016)
On their journeys through sea ice covered areas even vessels of high ice class or icebreakers could get into trouble. Reliable information from earth orbiting satellites could therefore be highly desirable. The German satellites TerraSAR-X (TSX) and TanDEM-X (TDX) are capable to deliver precise information about the ice cover, independent of the time of day and cloud coverage. The German Antarctic Receiving Station (GARS) O’Higgins of the German Aerospace Center (DLR) (Klügel, Höppner et al., Polar Record 51, 2015) is now equipped with near-real time (NRT) processing capability for the TSX/TDX data. Thus, because of this expansion of the overall TSX/TDX ground segment, it provides navigation guidance in NRT to research vessels in the Antarctic. By providing information products from synthetic aperture radar (SAR) acquisitions, DLR supports a crew to safely navigate through sea ice. For this purpose, the TSX/TDX data is received at GARS O’Higgins directly after the acquisition and is locally processed in near-real time. Subsequently, just about 60 minutes after the raw data is acquired from the satellite, the TSX/TDX information product is transferred via email from GARS O’Higgins to the ship. Such a product is generated up to twice a day.